An alpha-fetoprotein electrochemical immunosensor based on a carbon/gold bi-nanoparticle platform. Issue 47 (19th November 2018) - Idris, Azeez O.; Mabuba, Nonhlangabezo; Arotiba, Omotayo A.
Abstract : We report an electrochemical immunosensor for alpha-fetoprotein (AFP) on an immobilisation layer of carbon and gold bi-nanoparticles. XRD and immunosensor responses to 10 ng mL −1 alpha-fetoprotein: (a) GCE/antibody/BSA, (b) GCE/AuNPs/antibody/BSA, (c) GCE/CNPs/antibody/BSA, (d) GCE/CNPs/AuNPs/antibody/BSA. Abstract : We report an electrochemical immunosensor for alpha-fetoprotein (AFP) using an immobilisation layer of carbon and gold bi-nanoparticles. The carbon nanoparticles (CNPs) were prepared from candle soot while the gold nanoparticles (AuNPs) were electrochemically deposited. The immunosensor was prepared by the immobilisation of a probe anti-AFP (antibody) on a CNP/AuNP nanocomposite modified electrode for 40 min at 35 °C and subsequently blocked by bovine serum albumin (BSA). Cyclic voltammetry and electrochemical impedance spectroscopy (EIS) were used to investigate the immunosensor at each stage of preparation. The immunosensor was responsive to AFP over a concentration range of 0.005 to 1000 ng mL −1, with detection limits of 0.0019 ng mL −1 (square wave voltammetry) and 0.00175 ng mL −1 (EIS). The immunosensor exhibited good stability over a period of fourteen days when stored at 4 °C, and was selective in the presence of some interferents such as glucose, carcinoembryonic antigen, prostate-specific antigen, human immunoglobulin, etc. The presence of the bi-nanoparticles enhanced the immunosensor performance.